The Influence of Artificial Intelligence Perception on Accountants’ Adaptation in the Bangkok Metropolitan Area - อินเสือ อังคณา; ปาลีพัฒน์สกุล รุจิรัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: (1) analyze the influence of Artificial Intelligence (AI) technology on accounting practices; (2) examine the level of understanding of AI application; and (3) investigate the adaptation strategies of accountants in the Bangkok Metropolitan Area. The study employed a quantitative research design. Data were collected from a sample of 400 accountants using non-probability sampling based on Cochran’s (1977) approach. The research instrument was a structured questionnaire, and its reliability was tested using Cronbach’s alpha. Data were analyzed using descriptive statistics, including mean and standard deviation. The findings revealed that: (1) the overall impact of AI on accounting practices was at a moderate level. The dimension with the highest mean score was governance, transparency, and reliability, indicating that AI is perceived as a tool that enhances accuracy, reduces errors, and supports strategic decision-making. Meanwhile, the problems and obstacles in implementing AI in accounting organizations were also at a moderate level, with key issues including the lack of a clear digital strategy and a shortage of personnel with specialized expertise; (2) accountants’ understanding and utilization of AI were at a moderate level. Although they possessed basic knowledge of AI, they lacked in-depth training and systematic application skills; and (3) regarding adaptation strategies, accountants demonstrated positive attitudes toward AI and were able to adjust their work processes to align with the technology to some extent. However, they still lacked long-term professional development planning.